2014
DOI: 10.5505/tjtes.2014.95825
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure secondary to hepatic compartment syndrome: case report and literature review

Abstract: We report a case of a patient with a delayed large intrahepatic hematoma and transient decline in hemoglobin to 62 g/L 18 days after liver injury. Abdominal computed tomography revealed seriously flattening of inferior vena cava, which was consistent with compression by the enlarging hematoma. Although traditionally there was no indication for surgical intervention, the patient developed acute liver failure with a progressive increase in liver enzymes and bilirubin. We postulated the ever-expanding hematoma mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…If the patient is hemodynamically unstable, exploratory laparotomy with evacuation of the hematoma and conventional hemostasis techniques should be proposed, with perihepatic packing if bleeding persists (4,(16)(17)(18)(19). Hepatic angiography Critical Care Medicine www.ccmjournal.org e177 before and after image-guided aspiration of the hematoma in order to locate an eventual bleeding source to embolize represents another strategy, especially for stable patients or if open surgery is considered too risky (3,16). It may, however, not be sufficient, especially in case of clotting of the hematoma preventing aspiration.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…If the patient is hemodynamically unstable, exploratory laparotomy with evacuation of the hematoma and conventional hemostasis techniques should be proposed, with perihepatic packing if bleeding persists (4,(16)(17)(18)(19). Hepatic angiography Critical Care Medicine www.ccmjournal.org e177 before and after image-guided aspiration of the hematoma in order to locate an eventual bleeding source to embolize represents another strategy, especially for stable patients or if open surgery is considered too risky (3,16). It may, however, not be sufficient, especially in case of clotting of the hematoma preventing aspiration.…”
Section: Discussionmentioning
confidence: 98%
“…Proposed therapeutic algorithm for management of hepatic compartment syndrome (from ref [2,3,4,16,17,19]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 According to the new guidelines for the management of blunt liver trauma, laparotomy is only indicated if the patient is hemodynamically unstable and has signs of peritonitis. 19,20 Surgical and nonsurgical (e.g., endovascular intervention) management have the same recovery objectives in trauma cases, which are reducing massive bleeding and saving lives. 13 The complications from blunt liver trauma include hepatic artery pseudoaneurysms, which have a high risk for rupture and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…However, several disadvantages associated with nonoperative management have been reported: risk of missed intraabdominal injury; transfusion-related illness; and risks associated with embolization techniques including hepatic necrosis, abscess formation, and bile leak (3). Reports have found that intrahepatic or subcapsular hematoma can increase intrahepatic pressure, excluding the portal vein and inferior vena cava, resulting in marked hepatic dysfunction and obstructive shock in patients with hepatic injury who were treated nonoperatively (4)(5)(6)(7)(8). This pathological condition has been described as hepatic compartment syndrome (HCS) and is most commonly reported in young patients with hard hepatic capsules (9).…”
Section: Introductionmentioning
confidence: 99%